2015
DOI: 10.1248/bpb.b14-00740
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib Is Transported by the Organic Anion Transporter 1B1 and the Multidrug Resistance Protein 2

Abstract: Regorafenib is a small molecule inhibitor of tyrosine kinases, and has been shown to improve the outcomes of patients with advanced colorectal cancer and advanced gastrointestinal stromal tumors. The transport profiles of regorafenib by various transporters were evaluated. HEK293/organic anion transporting polypeptide 1B1 (OATP1B1) cells exhibited increased drug sensitivity to regorafenib. Regorafenib inhibited the uptake of Key words regorafenib; IC 50 ; multidrug resistance protein 2; organic anion transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…Recent investigations have demonstrated that regorafenib modestly inhibits the function of human OATP1B1, and that HEK293 cells overexpressing OATP1B1 exhibit increased sensitivity to regorafenib, suggesting that this multikinase inhibitor might be a transported substrate of Oatp1b‐type carriers in vivo . Our current studies, however, demonstrated that Oatp1b2 deficiency in mice does not cause differences in the pharmacokinetic profile of regorafenib after oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have demonstrated that regorafenib modestly inhibits the function of human OATP1B1, and that HEK293 cells overexpressing OATP1B1 exhibit increased sensitivity to regorafenib, suggesting that this multikinase inhibitor might be a transported substrate of Oatp1b‐type carriers in vivo . Our current studies, however, demonstrated that Oatp1b2 deficiency in mice does not cause differences in the pharmacokinetic profile of regorafenib after oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the organic-anion-transporting polypeptide (OATP) family ( SLCO genes) may be involved in the transport of TKIs used against HCC. OATP1B1 and OATP1B3 can mediate the uptake of cabozantinib [ 12 ], while OATP1B1 can also transport regorafenib [ 13 ] and probably lenvatinib [ 14 ]. However, there is a controversy regarding OATP-mediated sorafenib transport.…”
Section: Drug Uptake and Export (Moc-1)mentioning
confidence: 99%
“…The deregulation of the ADME genes involved in the metabolism and clearance of these two drugs may help to explain their relative efficacy. The key ADME genes involved in the metabolism and clearance of sorafenib and regorafenib in liver include the enzymes CYP3A4 (Ghassabian et al, 2012) and UGT1A9 (Peer et al, 2012;Miners et al, 2017), influx transporters (SLCO1B1, SLCO1B3, and SLC22A1) (Swift et al, 2013;Zimmerman et al, 2013;Ohya et al, 2015), and efflux transporters (ABCB1, ABCC2, and ABCG2) (van Erp et al, 2009;Ohya et al, 2015). While the efflux transporters were not significantly altered in HCC, the expressions of CYP3A4, UGT1A9, SLCO1B1, SLCO1B3, and SLC22A1 were all significantly downregulated in HCC, consistent with previous observations (Vander Borght et al, 2005;Tsuboyama et al, 2010;Heise et al, 2012;Ye et al, 2014).…”
Section: Deregulation Of Adme Genes In Hepatocellular Carcinomamentioning
confidence: 99%